Integrated Teaching Competency Framework for General Education Program: Suggestions and Recommendations for Natural Science Teachers - Thi Thu Hoai, Vu (VNU Journal of Science: Education Research; Vol 37 No 4DO - 10.25073/2588-1159/vnuer.4609, 2021)
This article investigated the general structure of teaching competencies and integrated teaching competencies of natural science teachers in high school education, the actual situation of integrated teaching in Vietnam and some other countries in the world, and the designing of assessment templates to recognize difficulties of natural science teachers in integrated teaching. It is shown that natural science teachers are facing various challenges in integrated teaching: a lack of professional knowledge and skills in building integrated topics and teaching with this approach, problems in putting integrated teaching techniques into practice. On this foundation, the article presents a procedure for building an integrated teaching competency framework for natural science teachers, then proposes such a framework. This framework consists of 4 competencies and ten criteria with detailed indicators. Natural science teachers can use this framework to develop tools (checklists, rating scales, or questionnaires) to assess their integrated teaching quality and their “colleagues”, henceforth fostering their competencies as required by the General Education Program.